2010
DOI: 10.5398/medpet.2010.33.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Population and Fermentation Characteristic in Response to Sapindus rarak Mineral Block Supplementation

Abstract: This experiment was conducted to evaluate the eff ect of supplementation with lerak extract combined with mineral block on protozoal and bacterial population, and fermentation characteristic in vitro. The experimental design was completely randomized block design with 3 treatments and 4 replications. Control diet was a substrate that consisted of concentrate, forage and feed block with ratio 50 : 48 : 2, respectively. The treatments as a substrate were: control diet (C), C + 0.09% lerak extract, and C + 0.18% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
2
Order By: Relevance
“…The biological activities of organic substances other than sugars, fatty acids or amino acids, have been identified in plant extracts such Achillea millefolium, Arnica montana, Lavandula officinalis, Equisetum arvense, Fagopyrum esculatum, Sativa officinalis and Solidago virgaurea (Duke, 1992). Suharti et al (2010) found that addition of lerak (Sapindus rarak) fruit extract up to 0.18% from total ration in the presence of mineral block mixture was not effective to depress protozoa population, but could modify fermentation characteristics in vitro. From all above Salem et al one can infer that plant secondary metabolites at the optimum doses can enhance GP, degradability, and general fermentation kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological activities of organic substances other than sugars, fatty acids or amino acids, have been identified in plant extracts such Achillea millefolium, Arnica montana, Lavandula officinalis, Equisetum arvense, Fagopyrum esculatum, Sativa officinalis and Solidago virgaurea (Duke, 1992). Suharti et al (2010) found that addition of lerak (Sapindus rarak) fruit extract up to 0.18% from total ration in the presence of mineral block mixture was not effective to depress protozoa population, but could modify fermentation characteristics in vitro. From all above Salem et al one can infer that plant secondary metabolites at the optimum doses can enhance GP, degradability, and general fermentation kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding animals on minerals mixture (MM) containing elements like Zn may activate the carbonic anhydrase enzyme which has, among others, the function of maintaining acid-base balance of rumen fluid in a normal pH (5.5 to 7.2) and making ruminal environments more stable and neutral, as stated by Owen and Goetsch (1998). However, there are limited reports on the effects of tree extracts combined with MM on ruminal gas production (GP) and nutrient digestibility (Suharti et al, 2010). The aim of this study was to determine the effects of using increasing levels of SB extract and a MM and their combination on in vitro GP and some ruminal fermentation parameters of a total mixed ration (TMR) made of concentrate with corn silage (50:50 DM basis).…”
Section: Introductionmentioning
confidence: 99%
“…Saponin merupakan detergen alami yang bermanfaat sebagai agen defaunasi protozoa (Wina et al, 2005). Penurunan jumlah protozoa yang bersilia akan meningkatkan aliran protein mikrob dari rumen, meningkatkan efisiensi penggunaan pakan, dan mengurangi metanogenesis (Suharti et al, 2010). Ditambahkan oleh Lilis (2012), defaunasi meningkatkan aliran masuknya asam amino ke duodenum, serta efisiensi pertumbuhan meningkat dan aliran protein pakan ke organ pasca rumen akan lebih banyak jika protozoa tidak ada…”
Section: Hasil Dan Pembahasanunclassified
“…Defaunasi dapat meningkatkan aliran protein ke organ pencernaan dibelakang rumen sebesar 18% (Merchen dan Titgemeyer, 1992). Penurunan jumlah protozoa yang bersilia akan meningkatkan aliran protein mikrob dari rumen, meningkatkan efisiensi penggunaan pakan, dan mengurangi metanogenesis (Suharti et al, 2010).…”
unclassified
“…For efficient use of anchovy proteins, other methods must be adapted for protein recovery, such as enzymatic hydrolysis, physical solutions, chemical solutions, and fermentation. Among these methods, enzymatic hydrolysis is widely used (Kim, Son, Maeng, Cho, & Kim, 2016;Suhartia, Kurniawatib, Astutia, & Wina, 2010). However, fermentation and especially SSF, has the characteristic of lower resource consumption and cost than enzymatic hydrolysis.…”
mentioning
confidence: 99%